2019
DOI: 10.1039/c8mh01100a
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous printing and deformation of microsystems via two-photon lithography and holographic optical tweezers

Abstract: Microstructures with embedded strain energy are fabricated by an advanced approach that combines two-photon lithography with holographic optical tweezers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The on‐demand assembly capability of optical tweezers with high spatial precision has also made it a versatile made‐to‐order tool for the design of complex superstructures in soft‐matter systems such as multicellular structures, [ 204 ] liquid crystals, and supermicelles, [ 46,205 ] and even functional microsystems themselves. [ 206 ] Fabrication of such superstructures and microsystems are general impossible via the conventional top‐down or bottom‐up approaches. Optical force enables the controllable assembly of these soft‐matter building blocks into hierarchical superstructures with high reconfigurability.…”
Section: Optical Forces For Biological Explorationmentioning
confidence: 99%
See 1 more Smart Citation
“…The on‐demand assembly capability of optical tweezers with high spatial precision has also made it a versatile made‐to‐order tool for the design of complex superstructures in soft‐matter systems such as multicellular structures, [ 204 ] liquid crystals, and supermicelles, [ 46,205 ] and even functional microsystems themselves. [ 206 ] Fabrication of such superstructures and microsystems are general impossible via the conventional top‐down or bottom‐up approaches. Optical force enables the controllable assembly of these soft‐matter building blocks into hierarchical superstructures with high reconfigurability.…”
Section: Optical Forces For Biological Explorationmentioning
confidence: 99%
“…For example, Chizari et al reported a fabrication technique combined TPL with HOTs to enable the fabrication of polymer‐based integrated microsystems with embedded strain energy. [ 206 ] Such technique allows the print‐and‐deform process to be synchronized and automated. TPL enables the printing of the basic parts of the system, while HOTs enable optical trap to be applied on the system for the assembly and actuation.…”
Section: Optical Forces For Biological Explorationmentioning
confidence: 99%
“…In the cases where the forces created by OT aren't enough to completely confine a specimen, OT have been combined with other trapping technologies such as acoustics, magnetic tweezers, microfluidics, and mechanical systems (Wuite et al, 2000;Neuman and Nagy, 2008;Thalhammer et al, 2016;Dholakia et al, 2020). OT share a lot of similarities with other systems which use tightly focused beams, including laser scissors (Greulich, 2007(Greulich, , 2017Difato et al, 2011;Berns, 2020) and two photon photopolymerization systems (Grier, 2003;Chizari et al, 2019). By using either different wavelengths, pulsed beams, or simply turning up the laser power, OT systems can be adapted for cutting cells, performing microsurgery (Berns, 2020), and fabricating microstructures for use as probes or OT operated micro-machines (Chizari et al, 2019).…”
Section: Optical Tweezersmentioning
confidence: 99%
“…OT share a lot of similarities with other systems which use tightly focused beams, including laser scissors (Greulich, 2007(Greulich, , 2017Difato et al, 2011;Berns, 2020) and two photon photopolymerization systems (Grier, 2003;Chizari et al, 2019). By using either different wavelengths, pulsed beams, or simply turning up the laser power, OT systems can be adapted for cutting cells, performing microsurgery (Berns, 2020), and fabricating microstructures for use as probes or OT operated micro-machines (Chizari et al, 2019).…”
Section: Optical Tweezersmentioning
confidence: 99%
“…To overcome these limitations, a number of variations of TPP have been explored . Out of these, the stimulated emission depletion (STED) approach is particularly promising and has demonstrated the smallest feature sizes, allowing for the fabrication of freestanding 3D structures with strut cross‐sectional dimensions as small as 120 × 170 nm with resolutions of 175 and 375 nm in the sense of Abbe and Sparrow, respectively .…”
mentioning
confidence: 99%